Guaranteeing Freedom of Speech: The Role of the Primus Inter Pares Principle in the Presidential Insult Clause - Muhammad Anugerah Perdana; Shafa Ataina Aurellia (Fakultas Hukum Universitas Lampung, 2025)
The ratification of Indonesia’s new Criminal Code (KUHP) on December 6, 2022, has sparked concerns over potential restrictions on human rights, particularly the right to freedom of expression. These concerns arise from the reintroduction of the article on insulting the president, which had been annulled by the Constitutional Court in Decision No. 013-022/PUU-IV/2006. The government contends that the revised provision is now grounded in the primus inter pares principle, which, according to the Minister of Law and Human Rights, seeks to uphold the president’s dignity without compromising public freedom of speech. This study employs a normative juridical methodology with statutory and comparative approaches to analyze how the primus inter pares principle in the presidential insult article can safeguard freedom of expression. The findings suggest that, while the principle is designed to prevent the misuse of presidential protections, its practical application remains unclear and susceptible to misinterpretation. Consequently, further clarification and judicial oversight are necessary to ensure an equitable balance between state dignity and individual rights.